Protein and cellulose level in diet. Effects on enzymatic activity, metabolite and amino acid profiles in freshwater anomurans Aegla uruguayana (Decapoda: Anomura) - Musin, Gabriela Eliana (2019)
The aims of this study were to evaluate the short-term effects of artificial diets with different protein: cellulose ratios (D1 = 60:0, D2 = 45:15 and D3 = 30:30) on the enzymatic activity and metabolite profile and to probe the suitability of the amino acid profile of the different diets in Aegla uruguayana. The different artificial diets affected the digestive total protease and amylase activities in a short period of time. Lipases were not affected by the diets. In the haemolymph, an effect of the diet was found in glucose and triglyceride measurements. Particularly, the glucose of the organisms fed D1 was significantly lower than that of organisms fed D2, without significant differences in D3. The concentrations of triglycerides were different among organisms subjected to the treatments, indicating a greater concentration in organisms fed D2 than in those fed D1. In muscle tissue, the concentration of glycogen followed the same trend as haemolymphatic glucose, indicating that the organisms fed D2 had a higher concentration of this metabolite compared to the rest. The amino acid profile of muscle tissue of wild and fed aeglids had a high and significant correlation in all cases, showing few changes in the short-term feeding regime. Some changes were observed mainly in aeglids fed D3, which exhibited the lowest amounts of methionine, lysine and arginine and the highest amounts of aspartic + glutamic acids. In addition, D2 has a good quality of EAA, fulfilling almost all the requirements of a wild aeglid.